2008
DOI: 10.1152/ajprenal.00366.2007
|View full text |Cite
|
Sign up to set email alerts
|

Treating lithium-induced nephrogenic diabetes insipidus with a COX-2 inhibitor improves polyuria via upregulation of AQP2 and NKCC2

Abstract: Prostaglandin E(2) may antagonize vasopressin-stimulated salt absorption in the thick ascending limb and water absorption in the collecting duct. Blockade of prostaglandin E(2) synthesis by nonsteroidal anti-inflammatory drugs (NSAIDs) enhances urinary concentration, and these agents have antidiuretic effects in patients with nephrogenic diabetes insipidus (NDI) of different etiologies. Because renal prostaglandins are derived largely from cyclooxygenase-2 (COX-2), we hypothesized that treatment of NDI with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 47 publications
4
51
0
2
Order By: Relevance
“…Second, induction of COX-2 by lactational exposure to TCDD, a polychlorinated polycyclic aromatic hydrocarbon, was shown to induce hydronephrosis in the neonate of rodents, but the administration of a selective inhibitor to COX-2 abolished such a pathogenesis (Nishimura et al, 2008). Our present study showed that LiCl injection induces an increase in COX-2 mRNA and an associated decrease in AQP2 mRNA (Norregaard et al, 2007;Kim et al, 2008) in the neonatal kidney (Fig. 2) and resulted in severe histopathological alterations leading to hydronephrosis.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Second, induction of COX-2 by lactational exposure to TCDD, a polychlorinated polycyclic aromatic hydrocarbon, was shown to induce hydronephrosis in the neonate of rodents, but the administration of a selective inhibitor to COX-2 abolished such a pathogenesis (Nishimura et al, 2008). Our present study showed that LiCl injection induces an increase in COX-2 mRNA and an associated decrease in AQP2 mRNA (Norregaard et al, 2007;Kim et al, 2008) in the neonatal kidney (Fig. 2) and resulted in severe histopathological alterations leading to hydronephrosis.…”
Section: Discussionmentioning
confidence: 47%
“…Potassium concentra--tion (Table 2). It has been reported that lithium administration affects kidney functions including diuresis in a COX-2-mediated manner (Rao et al, 2005), and that COX-2 negatively regulates gene expression of water channels such as AQPs 2 and 3, and transporters such as Na-K-2Cl cotransporter type 2 (NKCC2), in the kidney (Kim et al, 2008;Norregaard et al, 2007). In this context, we quantified mRNA of COX-2, AQP2, AQP3, and NKCC2 in the kidney from LiCl-injected mice and control mice on PND 7.…”
Section: Effects Of Licl On Developing Kidneymentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62] PGE2 activates the EP3 receptor in principal cells, leading to a reduced cAMP signaling, AQP2 expression, and plasma membrane targeting. 48,63 Importantly, renal PGE2 production is stimulated by flow-stimulated release of ATP and its degradation products by activation of their P2Y receptors.…”
Section: Toxic Effects Of Lithium Treatmentmentioning
confidence: 99%
“…[66][67][68][69] Prostaglandin synthase inhibitors are used because they increase the AQP-2 channels at apical membrane by increasing intracellular cAMP level. 70,71 The main side effect of these drugs is that they cause kidney damage and gastric problems. 11,72,73 Recent studies have shown that long term treatment with thiazides can cause renal carcinoma.…”
Section: Nephrogenic Diabetes Insipidusmentioning
confidence: 99%